Membranous nephropathy secondary to pulmonary tuberculosis - Mohammad Yasin; Khan, Mohsin; Faiza Khan; Niama Khan (Journal of the Pakistan Medical Association, 2026)
Glomerulonephritis (GN), secondary to tuberculosis, is quite a rare condition. Here we report the case of membranous nephropathy, which completely resolved after the treatment of tuberculosis. A 42-year-old man presented to a nephrologist with burning micturition. His urine routine examination (RE) was suggestive of 2+ protein. His 24-hour urinary protein was 4.2 grams. Renal biopsy revealed membranous nephropathy. His autoimmune, hepatitis B, hepatitis C, and HIV workups were non-conclusive. The nephrologist advised him to take Rituximab. Before the commencement of immunosuppressants, his Interferon-gamma Release Assay (IGRA) was tested which turned positive. He was referred to a pulmonologist for treatment of latent tuberculosis and further workup. His sputum geneXpert detected pulmonary TB. He was treated with anti-tuberculous therapy (ATT), and his proteinuria improved gradually and settled. The patient did not require any immunosuppressants for MN. The initial symptoms of MN secondary to TB are subtle. It is imperative to evaluate the cause of membranous nephropathy before starting an immunosuppressant. GN secondary to TB can be treated successfully with ATT. Key Words: Glomerulonephritis, Pulmonary tuberculosis, Rituximab, Antituberculosis therapy (ATT).